2017
DOI: 10.1002/asi.23929
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centered and experience‐aware mining for effective adverse drug reaction discovery in online health forums

Abstract: Adverse Drug Reactions (ADRs) have become a serious health problem and even a leading cause of death in the United States. Pre‐marketing clinical trials and traditional post‐marketing surveillance using voluntary and spontaneous report systems are insufficient for ADR detection. On the other hand, online health forums provide valuable evidences in a large scale and in a timely fashion through the active participation of patients, caregivers, and doctors. In this article, we present patient‐centered and experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Existing methods for drug discovery from online content extract drugs at post and statement level. ADR mining systems typically include a named entity recognition (NER) model and a relationship or semantic role labeling model [ 19 , 20 ]. Recent neural approaches address lexical variation in user-generated content – the difficulty faced by traditional keyword matching and rule-based approaches – to improve recognition and labeling components [ 21 , 22 ].…”
Section: Related Workmentioning
confidence: 99%
“…Existing methods for drug discovery from online content extract drugs at post and statement level. ADR mining systems typically include a named entity recognition (NER) model and a relationship or semantic role labeling model [ 19 , 20 ]. Recent neural approaches address lexical variation in user-generated content – the difficulty faced by traditional keyword matching and rule-based approaches – to improve recognition and labeling components [ 21 , 22 ].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the current technique for future action detection sometimes generates false positives. To address these issues, we will investigate how to leverage part-of-speech and reference resolution techniques [ 47 ] to improve natural language understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of previous campaigns on eHealth which focusses on addressing the differences that occur between medical terms in laymen queries and the extracted synonyms terms (expert vocabularies) had clearly shown that the task is challenging with a room for enhancement [10], [8], [16]. [22], [27] used the pre-marketing clinical trials and traditional post-marketing surveillance using voluntary and spontaneous report systems to determine the adverse drug reactions (ADRs) which has now become a major health challenge.…”
Section: Related Workmentioning
confidence: 99%